Sales Enablement Tools and Techniques for Modern Sales Organization - Kilian, Dietmar; Mirski, Peter; Lorenz, Britta (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
This book helps in building an optimally designed and customer-oriented sales organization. It places a special emphasis on purchasing decisions and leads to producing a decisive competitive advantage. The focus is on the sales enablement process as a holistic framework concept. It forms the infrastructure that ensures efficient cooperation between all areas of the company. The book explains the alignment of all goals, motivations, thought patterns, actions and campaigns in relation to the needs of the customer. In addition, it shows the most promising methods and approaches and how the practical start of sales enablement can look like. The book is aimed at managers and all who deal with sales strategies. .
Keywords: Customer relations -- Management; Sales management; Telemarketing; Internet marketing; Customer Relationship Management; Sales and Distribution; Digital Marketing